Regional Asset Utilization: How Can it Affect Regional Income and Poverty? - Rahman Hadi; Arief Maulana; Rama Mahesa; Rasidin Karo Karo Sitepu; Rindang Mustikawati (Economics Development Analysis Journal, 2024)
This study examines Indonesia’s regulatory framework and empirical practices regarding using regionally owned assets. By applying the two-stage least squares (2SLS) technique for the national macro model, the study also seeks to determine the effects of increased regional asset utilization on poverty reduction and regional revenue across various regions. The study employs a descriptive-analytical approach using mixed methods. Fixed effect and random effect estimation techniques were utilized for the regional models, while the two-stage least squares (2SLS) method was applied for the national macro models. The Statistical Analysis System (SAS), version 4.0, was used for this analysis. The findings demonstrate that maximizing the use of regional assets positively impacts regional original income, with a 1% increase in asset utilization leading to a 0.53% rise in regional original income. Furthermore, a 1% increase in regional income results in a 0.09% decrease in poverty. Increasing regional revenue and reducing poverty are two measurable outcomes of optimizing regional assets as a policy tool to enhance regional economic performance. Several factors contribute to Indonesia’s low optimization of asset utilization, including remote geographic locations, legal disputes with third parties, numerous assets unregistered in state or regional administrations, and unclear asset allocation